Capnocytophaga canimorsus - neobičajna povzročiteljica septičnega šoka pri bolniku brez vranice - Gorišek Miksić, Nina (Medicinski razgledi, 2002)
The paper describes the case of a 28-year-old patient without a spleen in whomhigh fever, vomiting, abdominal cramps, palpable purpura and peripheral cyanosis suddenly developed. Upon admission, he was in septic shock with multi-organ failure. He needed intubation, artificial ventilation and hemodynamic support. Blood culture samples grew gram-negative rods after four days of incubation, which were later identified as Capnocytophaga Canimorsus. In continuation, the differential diagnosis in patients without a spleen who suddenly develop a septic shock is discussed. The importance bf taking an exact exposure history to find the correct diagnosis is emphasized, including possible contacts with domestic animals.
Keywords: Splenektomija; Splenic Rupture; Splenectomy; Vranica, ruptura; Shock, Septic; Šok septični; Capnocytophaga; Odrasli; septični šok; Adult; diagnostika; infekcije; vranica